2020
DOI: 10.7705/biomedica.5833
|View full text |Cite
|
Sign up to set email alerts
|

Hallazgos incidentales de COVID-19 en tomografías PET/CT 18F-FDG de pacientes asintomáticos con cáncer en dos instituciones de salud de Bogotá, Colombia

Abstract: La COVID-19 es la infección viral causada por el SARS-CoV-2 y declarada por la Organización Mundial de la Salud (OMS) como pandemia. Los pacientes con cáncer tienen un mayor riesgo de adquirir la infección y un peor pronóstico, ya que deben asistir a visitas médicas en diferentes centros hospitalarios, reciben tratamientos médicos y quirúrgicos y deben someterse a estudios diagnósticos como la PET/CT en servicios de medicina nuclear, lo que es ocasión para el hallazgo incidental de la infección.Se presentan la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…We observed that each database identified unique keywords that did not appear in other databases and that those keywords were linked to specific articles related to MRI or PET/CT. In the Total link strength table, the words that caught our attention were PubMed [incidental findings [ 84 ], adolescent [ 85 ]]; Scopus [case report [ 86 ]]; and WoS [encephalitis [ 87 ], stroke, [ 88 ] microbleeds [ 89 ], myocarditis [ 90 ]].…”
Section: Discussionmentioning
confidence: 99%
“…We observed that each database identified unique keywords that did not appear in other databases and that those keywords were linked to specific articles related to MRI or PET/CT. In the Total link strength table, the words that caught our attention were PubMed [incidental findings [ 84 ], adolescent [ 85 ]]; Scopus [case report [ 86 ]]; and WoS [encephalitis [ 87 ], stroke, [ 88 ] microbleeds [ 89 ], myocarditis [ 90 ]].…”
Section: Discussionmentioning
confidence: 99%